Hemostasis features in pregnant women with hypertensive disorders living in the highlands of Tadzhikistan Republic - N. A. Tadzhiboeva; A. G. Yashchuk; I. B. Fatkullina; S. A. Galeeva; A. Yu. Lazareva; N. A. Stetsenko; D. G. Sitdikova (Акушерство, гинекология и репродукция)
Introduction. One of the actual problems of modern obstetrics is hypertensive disorders during pregnancy. Pregnant women living in highlands are exposed to adverse factors, the most important of which is decreased oxygen in the air. Hypertension of pregnant women in high altitude conditions is conjoin with exogenous hypobaric hypoxia, and as a total organ pathology leads to functional and morphological changes in all organs and systems.Aim: to study the features of hemostasis system in pregnant women with hypertensive disorders in highlands.Materials and Мethods. A prospective comparative study included 114 pregnant women with hypertensive disorders, which were divided into 2 groups: group 1 – 63 pregnant women living in highlands, and group 2 – 51 pregnant women living in lowlands. In group 1, 42 pregnant women (67 %) and in group 2, 24 (47 %) pregnant women were diagnosed with severe preeclampsia. Hemostasis parameters were studied: blood clotting time, prothrombin index, content of fibrinogen and soluble fibrin-monomer complexes (SFMC), international normalized ratio (INR), activated partial thromboplastin time (APTT) index, thrombin time, platelet count.Results. In pregnant mountaineers, compared with pregnant women in lowlands, a higher content of such hemostasis parameters as APTT index (1.654 ± 0.426 vs. 0.892 ± 0.1145; p < 0.001) and SFMC level (4.921 ± 0.753 mg% vs. 3.590 ± 0.5676 mg%; p < 0.001), thrombin time values (103.206 ± 3.734 seconds vs. 93.920 ± 7.8268 seconds; p < 0.001) were revealed, as well as lower fibrinogen concentration (3.762 ± 0.809 g/l vs. 4.160 ± 1,3015 g/l; p = 0.048).Conclusion. In pregnant women living in highlands compared with pregnant women in lowlands with the addition of severe forms of preeclampsia (67 % vs. 47 %) hypercoagulation characteristic of normal pregnancy disappears, but, on the contrary, iso- and hypocoagulation appears.